DSN enzyme recognition initiated rolling circle amplification (DiRCA) for accurate miRNA detection in immune response and immune repair after trauma - Yi Mei; Jun Zhang; Li Zhu; Tianjiao Li; Hong Zhou; Mingjia Xie; Dongmei Zeng; Yajun Gou (Journal of Analytical Science and Technology, 2023)
Abstract Recent studies have reported that miRNA plays an important role in immune response and immune repair after trauma. By regulating the expression of related target genes, miRNA regulates the production, proliferation, development and immune response of immune cells. Therefore, it is in urgent demand to develop an novel method for miRNA analysis. Rolling circle amplification (RCA), as an attractive isothermal signal amplification strategy, has been widely utilized in constructing miRNA detection assays. However, accurate and sensitive miRNA quantitative determination remains a huge challenge for RCA based approaches. Herein, we propose a DSN enzyme based signal cycle initiated Rolling Circle Amplification assay (DiRCA) for sensitive and accurate miRNA detection. In DiRCA, target miRNA unfolds hairpin structure probe in the detection scaffold, forming a RNA–DNA duplex. DSN enzyme is utilized to specifically digest the DNA sequence in RNA–DNA duplex, releasing miRNA to form a signal cycle; its capability to distinguish one base pair mismatch in RNA–DNA duplex endows DiRCA a high selectivity. Meanwhile, DSN enzyme based cleavage initiates RCA, transcribing G-rich sequences for signal generation. Based on the DSN assisted signal cycle and RCA, DiRCA shows a low limit of detection of 0.43 fM and a superior capability in selectively detecting mismatched miRNA sequences, showing a promising prospect in the early-diagnosis of disease.